Effects of Peyton's four-step approach on objective performance measures in technical skills training: a controlled trial - Krautter, Markus; Weyrich, Peter; Schultz, Jobst-Hendrik; Buß, Sebastian Johannes; Maatouk, Imad; Jünger, Jana; Nikendei, Christoph (Teaching and learning in medicine, 2011)
Background: Although skills-lab training is widely used for training undergraduates in technical procedures, the way in which clinical skills are to be used and instructed remains a matter of debate. Purpose: We conducted a randomized controlled trial to evaluate the learning outcome of two different instructional approaches in the context of acquiring procedural-technical skills. Methods: Volunteer 2nd- and 3rd-year medical students were randomly assigned to an intervention group receiving instruction according to Peyton's Four-Step Approach (IG; n = 17) or to a control group receiving standard instruction (CG; n = 17). Both groups were taught gastric-tube insertion using a manikin. Following each of the two forms of instruction, participants’ first independent gastric-tube insertions were video recorded and scored by two independent video assessors using binary checklists and global rating forms. The time required for each instructional approach and for the first independent performance of the skill was measured. Results: A total of 34 students agreed to participate in the trial. There were no statistically significant group differences with regard to age, sex, completed education in a medical profession, or completed medical clerkships. The groups did not differ in terms of correct stepwise performance of the procedure as assessed by a binary checklist (p < .802). However, ratings based on global rating scales assessing professionalism and accompanying patient-doctor communication proved significantly better in IG (both ps < .001). The length of the different instructional approaches did not differ significantly between the two groups (IG: 605 ± 65 s; CG: 572 ± 79 s; p < .122), but the time needed for the first independent performance of gastric-tube placement on the manikin was significantly shorter in IG (IG: 168 ± 30 s; CG: 242 ± 53 s; p < .001). Conclusions: Peyton's Four-Step Approach is superior to standard instruction with respect to professionalism and accompanying doctor-patient communication and leads to faster performance when trainees perform the learned skill for the first time.
Gesehen am 08.07.2022